The role of social media content quality and online reviews in shaping hotel room booking decisions: Evidence from Swiss-Belhotel Rainforest Kuta, Bali - I Komang Karisma Adinata; Ida Bagus Sanjaya; Majid Wajdi; Dr. Muhammad Ahmad Mazher; Md. Afsarul Islam; Muhammad Waheed (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study aims to examine the influence of social media content quality and online reviews on customers' hotel room booking decisions at SBR Kuta, Bali. A quantitative research design was employed using purposive sampling to select hotel guests who had viewed the hotel's social media platforms and online review websites before making a reservation. Data were collected through a structured questionnaire based on a five-point Likert scale, measuring social media content quality, online review quality, and booking decision variables. The data were analysed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, the coefficient of determination (R²), and hypothesis testing through t-tests and the F-test to evaluate both partial and simultaneous effects. The results indicate that high-quality social media content and credible online reviews positively and significantly influence customers' booking decisions, both individually and collectively. These findings suggest that informative, engaging digital content and positive customer reviews strengthen consumer trust and increase booking intentions. Therefore, hotels should optimise their digital marketing strategies and actively manage online reviews to enhance marketing performance and improve booking conversions in the competitive hospitality industry.